Harnessing Antimicrobial Power: Innovative Strategies and Global Standards in Polymer Applications - Saleh Alkarri (Chemical and Materials Sciences - Developments and Innovations Vol. 3, 2024)
In the quest to combat microbial threats and enhance public health safety, the innovative field of antimicrobial polymers emerges as a beacon of hope. This chapter delves into the cutting-edge development of these polymers, which are ingeniously designed to thwart the proliferation of harmful microorganisms. By exploring the myriad of surface modification techniques, the chapter illuminates the pathways through which polymers acquire their disease-fighting capabilities. It further elucidates the intricate mechanisms by which these materials wage war against a spectrum of pathogens, including bacteria, viruses, and fungi. The discourse extends to a critical examination of international testing standards, ensuring that these revolutionary materials are rigorously evaluated for efficacy. Moreover, the paper addresses the paramount concern of toxicity, particularly when these polymers are employed in sensitive sectors such as healthcare and food packaging. Through this comprehensive review, the article under-scores the pivotal role of antimicrobial polymers in safeguarding our future and advancing the frontiers of material science.